Mechanical characterisation of kenaf/PALF reinforced composite-metal laminates: effects of hybridisation and weaving architectures - Ng, Lin Feng; Dhar Malingam, Sivakumar; Chen, Wei Ping (SAGE Publications Ltd., 2021)
Fibre metal laminates are advanced sandwich materials that offer various outstanding properties over conventional metallic alloys and composites. This research study intends to investigate the effects of weaving architectures and stacking configurations on the mechanical properties of fibre metal laminates based on kenaf/pineapple leaf fibre. Fibre metal laminates were fabricated through the hot moulding compression technique. Mechanical tests were performed on the kenaf/pineapple leaf fibre-based fibre metal laminates. In accordance with the findings obtained, hybridisation had led to the improvement in the mechanical properties of fibre metal laminates in comparison with [K/K/K] fibre metal laminates. Overall, twill woven-ply [P/P/P] fibre metal laminates showed the highest tensile and flexural strength, which was 14.53% and 33.50% higher than twill woven-ply [K/K/K] fibre metal laminates, respectively. Besides, the twill woven-ply [P/P/P] fibre metal laminates also displayed the highest impact strength and indentation properties compared to other non-hybrid and hybrid fibre metal laminates. When comparing the fibre metal laminates with different weaving architectures, twill woven-ply fibre metal laminates were shown to have higher mechanical properties over those of plain woven-ply fibre metal laminates.